Internet of vehicles empowered by edge intelligence - Yan ZHANG; Ke ZHANG; Jiayu CAO (物联网学报)
By pushing computing,storage and other resources to the proximity of end devices,edge intelligence empowers network edge entities powerful information processing and content delivery capabilities,while providing efficient and low-latency service support for the development and implementation of novel mobile services.Thus,edge intelligence is profoundly changing the functions of mobile applications and the utilization patterns of network resources.The application of edge intelligence technology in vehicular networks was studied firstly,and the core scientific problems that need to be solved in designing an efficient vehicular edge system was presented.Then,the technical challenges faced in solving these problems were analyzed and the corresponding solution strategies were given.